2015
DOI: 10.1088/2040-8978/17/12/125802
|View full text |Cite
|
Sign up to set email alerts
|

A bow-tie photoconductive antenna using a low-temperature-grown GaAs thin-film on a silicon substrate for terahertz wave generation and detection

Abstract: This paper presents heterogeneously integrated bow-tie emitter–detector photoconductive antennas (PCAs) based on low-temperature grown-gallium arsenide (LTG-GaAs) thin-film devices on silicon-dioxide/silicon (SiO2/Si) host substrates for integrated terahertz (THz) systems. The LTG-GaAs thin-film devices are fabricated with standard photolithography and thermal evaporation of metal-contact layers of chromium (Cr), nickel (Ni) and gold (Au). They are etched selectively and separated from their growth GaAs substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…These components were fabricated using a multi-step process involving photolithography, gold (Au) sputtering, and wet-etching. The process is detailed in other works 32 , but we summarize it here for completeness. The desired LT-GaAs layer is grown on a sacrificial AlAs layer on a semi-insulating GaAs substrate.…”
Section: Methodsmentioning
confidence: 99%
“…These components were fabricated using a multi-step process involving photolithography, gold (Au) sputtering, and wet-etching. The process is detailed in other works 32 , but we summarize it here for completeness. The desired LT-GaAs layer is grown on a sacrificial AlAs layer on a semi-insulating GaAs substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Further work by Awad et al [101] and later by Rios et al [98,106] both revealed how this bonding technique can be used to construct PCA array features. In the latter of these, 2 µm thick LT-GaAs is removed from its SI-GaAs growth substrate and bonded with SiO 2 -on-Si [106].…”
Section: Lt-gaas On Insulating Substratesmentioning
confidence: 99%
“…It can then undergo epitaxial liftoff (ELO) from its growth substrate and van der Waals forces can be used to bond the LT-GaAs film, typically 0.5-3 µm thick, to a new host substrate. This technique has been shown to work with various materials including Si [98], glass [99,100], sapphire [99][100][101], quartz [102], LiNbO 3 , InP, and diamond [103]. In the early works of Heiliger et al [99,100], 0.5 µm thick LT-GaAs films were transferred onto both sapphire and glass substrates.…”
Section: Lt-gaas On Insulating Substratesmentioning
confidence: 99%
“…These components were fabricated using a multi-step process involving photolithography, gold (Au) sputtering, and wet-etching. The process is detailed in other works 28 , but we summarize it here for completeness. The desired LT-GaAs layer is grown on a sacrificial AlAs layer on a semi-insulating GaAs substrate.…”
Section: Fabricationmentioning
confidence: 99%